Masking Ability of Various Metal Complexing Ligands at 1.0 mM Concentrations on the Potentiometric Determination of Fluoride in Aqueous Samples - Sakuni M. De Silva; Samitha Deraniyagala; Janitha K. Walpita; Indira Jayaweera; Saranga Diyabalanage; Asitha T. Cooray (Journal of Analytical Methods in Chemistry)
Fluoride is a common anion present in natural waters. Among many analytical methods used for the quantification of fluoride in natural waters, potentiometric analysis is one of the most widely used methods because of minimum interferences from other ions commonly present in natural waters. The potentiometric analysis requires the use of ionic strength adjusting buffer abbreviated as TISAB to obtain accurate and reproducible data. In most of the reported literature, higher concentrations of strong metal chelating ligands are used as masking agents generally in the concentration range of 1.0 to 0.01 M. In the present study, effectiveness of the masking agents, phosphate, citrate, CDTA ((1,2-cyclohexylenedinitrilo)tetraacetic acid), EDTA (ethylenediaminetetraacetic acid) HE-EDTA ((hydroxyethyl)ethylenediaminetriacetic acid)), triethanolamine, and tartaric acid at 1.0 mM in TISAB solutions was investigated. The experimental data were compared with a commercially available WTW 140100 TISAB solution as the reference buffer. According to the experimental data, the reference buffer always produced the highest fluoride concentrations and the measured fluoride concentrations were in the range of 0.611 to 1.956 mg/L. Out of all the masking agents investigated, only CDTA performed marginally well and approximately a quarter of the samples produced statistically comparable data to the reference buffer. All the other masking agents produced significantly low concentrations compared to the reference buffer. The most probable reasons for the underestimation of fluoride concentrations could be shorter decomplexing time and lower masking agent concentrations.